OncoDaily News Feature: Researchers identified a substantial presence of peripherally induced Treg cells in the tumor microenvironment - Sang Nee, Tan (OncoDaily, 2025)
This OncoDaily news feature highlights commentary by John Gordon on the study “Regulatory T cells converted from Th1 cells in tumors suppress cancer immunity via CD39,” published in the Journal of Experimental Medicine. The report summarizes key findings led by Sang-Nee Tan et al., including the identification of peripherally induced Treg cells in the tumor microenvironment, their conversion from Th1 cells via TGF-β signaling, and their CD39-dependent suppression of antitumor immunity.